Self-care of chronic illness prevents the risk of diabetic foot ulcers in patients with diabetes: a cross-sectional study - Joeliantina, Anita; Adji Norontoko, Dwi; Adinata, Ach. Arfan; Ragayasa, Adivtian; Nurul Hamid, Irfany (Jurnal Ners, 2024)
Introduction: Diabetic foot ulcer (DFU) is a serious and chronic complication of diabetes mellitus (DM). This study aims to explain a model of self-care of chronic illness on the prevention of DFU risk in patients with DM, including foot self-care of maintenance, monitoring, and management. Methods: This study was an analytical study with a cross-sectional approach, with 300 patients randomly selected from six Public Health Centers in Surabaya, Indonesia, from June to August 2022. The inclusion criteria were individuals with DM and aged more than 26 years. Exclusion criteria were reading disabilities or having cognitive impairments Data were collected using a questionnaire. The correlation between variables was analyzed using the statistical method  of Partial Least Squares. Results: The risk of DFU in patients with DM was 40% with low risk, 38% with moderate risk, 8% with high risk, 5% remission, and 10% with DFU. This research shows that there is a significant correlation between foot self-care management and the risk of DFU, where the p-value = 0.000, while the indicators of foot self-care maintenance and self-care monitoring do not have a significant correlation with the risk of DFU, where the p-value is respectively equal to 0.350 and 0.844. Conclusions: Foot self-care management was a factor that directly correlates with the risk of DFU. Autonomous self-care management behaviors still needed to be improved, because most patients still had these inadequate behaviors. Further research is needed to improve the behavior quality of patients with DM in managing foot care independently.